Effectiveness of online counselling during COVID-19 in Zambia: clients' and therapists' perspectives - Choongo Mulungu; Tafadzwa Mindu; Kelvin Mulungu (BMC Psychology, 2024)
Abstract Population-based studies have shown that a growing number of counsellors have been providing counselling via the Internet. There are mixed findings regarding the effectiveness of online counselling compared to traditional face-to-face counselling and other modalities. During the COVID-19 outbreak, online counselling services were advanced as the only safe means of attending to mental health conditions, especially during the lockdowns. However, the effectiveness of online counselling remains unclear, especially in developing countries with low digital literacy and poor Internet connectivity. This study's main purpose was to investigate and determine the clients' and therapists' perspectives on the effectiveness of online counselling during the pandemic based on the level of preparedness, mode of delivery, and challenges faced. The study used mixed methods employing a parallel convergent design and collected data from 284 participants (44 therapists and 240 counselling clients). The study found that therapists were not prepared to offer online counselling services, but were compelled by high demands for counselling services from clients during the pandemic. Both clients and therapists cited the cost of data bundles to connect to the Internet as a major barrier. Furthermore, both clients and therapists indicated that the most effective platform was video conferencing. The findings also show that therapists observed slowed progress in the client's recovery due to clients missing sessions. Logistic regression results on factors associated with preparedness and positive perception of online counselling showed that older therapists and lay counsellors were less likely to be prepared and evaluate sessions as less effective, respectively. Living in Lusaka (the capital) was associated with higher odds of perceiving online counselling as effective. Client results showed that older clients had lower odds of being prepared, and the counsellor being prepared increased the odds of the online counselling being perceived as effective. The researchers conclude that online counselling, in the context of a developing country, is ineffective because of the cost of Internet connection, the multiplicity of information communication technology (ICT) channels, low digital literacy, and lack of knowledge or experience using these platforms.